Etude de la variabilité agronomique et biochimique des quatre génotypes d’une variété de blé dur cultivé en Algérie (Triticum durum Desf.) - Fatima, Chehili; Leila, Boudour; Karima, Bouchtab (European Scientific Journal, ESJ, 2017)
The present study deals with four genotypes belonging to the Algerian durum wheat melanopus variety. In the experiment carried out in the greenhouse at Mentouri Constantine1Chaâbat Ersas University, it is measured the morpho-physiological parameters (stem height, cervical length, ear, barbs, leaf area, relative content Water yield and chlorophyll); the yield parameters (number of grains, number of spikelets per spike and weight of one thousand grains) and the biochemical parameters (total protein). From the results of the morphological parameters, it appears that the genotypes differ essentially by the leaf area. For the physiological parameters: total chlorophyll content and relative water content, no variation between the four genotypes was observed. As for the biochemical study evaluated by the total proteins, this made it possible to better differentiate the 4 genotypes and showed a remarkable intra-varietal polymorphism.